Novel anti fouling mixed matrix CeO2/Ce7O12 nanofiltration membranes for heavy metal uptake. Issue 2 (April 2018) - Jamil, Tarek S.; Mansor, Eman S.; Abdallah, Heba; Shaban, Ahmed M.; Souaya, Eglal R.
Abstract: Nanofilraion membranes (NF) were fabricated by an incorporation of CeO2 /Ce7 O12 nanoparticles with various loads via phase inversion method. The prepared cerium oxide nanoparticles and fabricated mixed matrix membranes were recognized by using x-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, surface charge studies and contact angle. The performances of the fabricated membranes were carried out using 100 mg/L/each aqueous solutions of Fe(NO3 )3, Al2 (SO4 )3, Co(NO3 )2, Cd(NO3 )2, Cu(NO3 )2 . The antifouling properties of the mixed matrix membranes were studied using 300 mg/L humic acid as foulant. The morphologies of the fabricated membranes have been affected by the presence of CeO2 /Ce7 O12 nanoparticles, as fillers, in the casting solution. Since, the four mixed matrix fabricated membranes of different nanoparticles loads have different skin porosities and macro-void structures. The mixed matrix NF membrane of 1 wt% had the lowest irreversible fouling ratio (1.1%) and high antifouling potential with highest flux recovery after humic acid filtration with less change in the rejection. The absence of the used nanoparticales in treated water as well as non toxic properties indicates that the fabricated membranes are safe to be used for filtration.